Ways of translation of ‘spirituality’ terms in English and Uzbek languages - Akhmedova Mehrinigor Bahodirovna (Proceedings of The ICECRS, 2019)
"Spirituality" consists of abstract concepts, it is difficult for a translator to find or choose the exact alternative to the unit. In the process of translation, the equivalent of one language unit may not be available in another language. In this case, the translation is expressed by a unit word or peripheral. These criteria are analysed in the article.